Validation of the CIDOC CRM using both extended graphical and category theory representations : includes two New Zealand case studies : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Information Systems at Massey University, Palmerston North, New Zealand - Zhou, Jia (Massey University, 2004)
There is considerable interest in the use of the Internet to retrieve and integrate multimedia information from centres of cultural heritage such as museums and art galleries. The ultimate desire of most devotees of cultural matters is to have universal access, through a single portal, to detailed information from sites throughout the world. This level of interoperability is not an easy task both technically and culturally. To provide an avenue where some of the technical problems of accessing information from a huge range of unique database environments can be resolved, a semantic conceptual reference model (CRM) was proposed by The International Committee for Documentation of the International Council of Museums (ICOM-CIDOC). The model provides definitions and a formal structure for describing the implicit and explicit concepts and relationships used in cultural heritage documentation. It is intended to provide a common and extensible semantic framework to which any cultural heritage information can be mapped. In this research two methods are proposed and developed to support the validation of the Conceptual Reference Model. The methodologies, one graphical and the other based on category theory, are used to replicate three published international validation activities and two new validations based on information supplied by two New Zealand heritage sites. This report also includes a literature review describing the main ideas and structures that form the basis of the CRM.
Keywords: Museums and the web; Semantic networks (Information theory); Ontologies (Information retrieval)